# Solve: 6x + 3y = 7xy and 3x + 9y = 11xy.

The given equations are 6x + 3y = 7xy and 3x + 9y = 11xy.

Dividing by xy on both sides of the given equations, we get

Then,

… (1)

… (2)

If we substitute and in (1) and (2), we get

3p + 6q = 7 … (3)

9p + 3q = 11 … (4)

Now by elimination method,

Step 1: Multiply equation (3) by 3 and equation (4) by 1 to make the coefficients of x equal.

Then, we get the equations as:

9p + 18q = 21 … (5)

9p + 3q = 11 … (6)

Step 2: Subtract equation (6) from equation (5),

(9p – 9p) + (3q – 18q) = 11 – 21

- 15q = - 10

Step 3: Substitute q value in (3),

3p = 3

p = 1

We know that and .

Substituting values of p and q, we get

x = 1 and y =

The solution is x = 1 and y = .

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Dealing With the Real Life Problems53 mins
Quiz | Solution of Linear Equations53 mins
Champ Quiz | Consistency and Inconsistency of Solutions36 mins
Pair of Linear Equations in Two Variables46 mins
Quiz | Real Life Problems Through Linear Equations56 mins
Smart Revision | Important Word Problems37 mins
Dealing with the Real Life Problems54 mins
Elimination (quicker than quickest)44 mins
Bonus on Applications of Linear Equations in Two Variables43 mins
HOT Topics of Applications of Linear Equations in Two Variables52 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Solve for x and y:

RS Aggarwal - Mathematics